Correlation-regression analysis of meteorological data from ultrasonic weather stations; Proceedings of SPIE; Vol. 11916 : Atmospheric and Ocean Optics: Atmospheric Physics - Botygin I. A. Igor Aleksandrovich; Volkov Yu. V.; Proskurov V. A.; Sherstnev V. S. Vladislav Stanislavovich; Sherstneva A. I. Anna Igorevna (2021, 2021)
Title screen